14‐3: Extremely Short‐Channel LTPS TFT Technologies for High‐Performance Low‐Power, and Reliable AMOLED displays. Issue 1 (28th June 2022) - Kim, Keunwoo; Chu, Jaehwan; Lee, Dokyeong; Kim, Doona; Kim, Hanbit; Sung, Bummo; Shin, Jiyoung; Oh, Yunjung; Kwak, Hyena; Choi, Sanggun; Lim, Junhyung; Kang, Taewook; et al.
Abstract : This paper presents recent progress to scale down low‐temperature polysilicon (LTPS) TFT technologies in the extremely short‐channel length regime for AMOLED displays. Process integration of short‐channel gate and narrow‐width polysilicon into scaled equivalent gate‐oxide thickness (EOT), is explored, in conjunction with enhanced poly crystallization by reducing defect density‐of‐state (DOS) especially in the grain boundaries of the channel region. We obtain more than twice higher current drive (Ion ) with significantly‐reduced parasitic gate capacitance, thereby enabling high‐performance high‐frequency panel operations. In addition to superior panel performance in scaled LTPS TFTs, reliable devices are attained, demonstrating robust device characteristics for negative‐bias instability (NBTI) and hot carrier injection (HCI) effects. Physics‐based analysis, based on experimental data and numerical device simulations, is performed to gain more insight in the TFT technologies.